Electron microscopic analysis method for measuring thickness of nano-scale material
The electron microscopy analysis method using focused ion beam preparation and electron energy loss spectrum calibration addresses the limitations of existing methods, providing high-precision thickness measurement and three-dimensional analysis of nanoscale materials.
Patent Information
- Application Number
- CN202411265904.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-03
AI Technical Summary
Existing methods for nanometer-scale thickness measurement of transmission electron microscope samples suffer from limitations such as narrow applicability, low accuracy, and reliance on specific sample conditions, leading to inaccurate measurements of materials like metals and non-conductive materials.
An electron microscopy analysis method involving focused ion beam preparation of needle-shaped samples, electron energy loss spectrum collection, zero-peak calibration, and data fitting to establish a calibration relationship for precise thickness measurement.
The method achieves high-precision, wide-range thickness measurement with nanoscale resolution, improving accuracy by up to 28% and enabling analysis of three-dimensional spatial scale and volume density information of nanoscale materials, including metals and non-conductive materials.
Smart Images

Figure CN119245566A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of transmission electron microscope microscopic analysis of materials, and in particular to an electron microscopic analysis method for measuring the thickness of nanometer-level materials. Background Art
[0002] The measurement of nanometer-scale material thickness is of vital importance to materials science and nanotechnology research. Accurately measuring the thickness of a material at a specific location is not only a prerequisite for characteristic plane analysis, but also a basis for providing key data for calculating the volume density of microstructures such as precipitated phases, crystal defects, pores, and bubbles in the material. In the routine observation of transmission electron microscope samples, especially for thin areas of the sample, the thickness is usually between 5 and 200 nanometers, which places extremely high precision requirements on the measurement technology.
[0003] At present, a variety of methods have been used to achieve nanometer-level thickness measurement of transmission electron microscope samples, including transmission electron microscope microanalysis technology, contamination point separation method, convergent beam diffraction method and X-ray energy spectrometry. These methods all have their specific applicable conditions and limitations. For example, transmission electron microscope microanalysis estimates the thickness of the sample by contrast changes. The measurement accuracy of the thickness of the crystal sample may reach the order of a few nanometers, but the sample needs to be very thin, usually not more than hundreds of nanometers. The accuracy of the convergent beam diffraction method can reach the order of nanometers or sub-nanometers, but the sample is usually required to be crystalline, and there are high requirements for the flatness and preparation quality of the sample. The accuracy of the contamination point separation method is about a dozen nanometers, but it is limited by the degree of sample contamination and the accuracy of tilt. The accuracy of the X-ray energy spectrometry is relatively low, and the measurement of some local areas with large component fluctuations is not accurate enough. In addition, patent CN 110986802 A uses sample twin plane modeling to quickly obtain the thickness of the transmission sample, but the sample to be measured must be a crystal containing twins. Patent CN 108317988 A obtains the thickness of the sample by adjusting the focal length of the transmission electron microscope objective lens, but this method relies on the naked eye to judge the upper and lower surfaces of the sample imaging, and has poor accuracy.
[0004] Therefore, a new electron microscopy analysis method is urgently needed to improve the accuracy of nanoscale thickness measurement of transmission electron microscopy samples. Summary of the invention
[0005] In view of this, the purpose of this application is to provide an electron microscopy analysis method for measuring the nanoscale thickness of transmission electron microscope samples, so as to accurately obtain the three-dimensional spatial scale information of nanoscale materials and the three-dimensional spatial volume density information of internal defects.
[0006] This application specifically adopts the following technical solutions:
[0007] An electron microscopic analysis method for measuring the thickness of nanometer-scale materials comprises the following steps:
[0008] S10, preparation of nanometer-scale needle-shaped transmission electron microscope samples by focused ion beam method;
[0009] S20, taking transmission electron microscope images to obtain the accurate thickness of different areas of the nanometer-scale needle tip;
[0010] S30, collecting electron energy loss spectra of different regions of nanometer-scale needle-tip electron microscope samples;
[0011] S40, the measured thickness of different regions of the nanometer-scale tip electron microscope sample is analyzed after zero peak calibration of the electron energy loss spectrum;
[0012] S50, obtaining a calibration relationship between the accurate thickness and the measured thickness through data fitting;
[0013] S60. Collect electron energy loss spectra of other samples of interest with the same composition as the nano-scale needle-tip electron microscope sample to obtain thickness data, use a calibration relationship to correct the thickness data, and obtain nano-scale thickness measurement of the material.
[0014] This method can accurately analyze the thickness of nanoscale materials, which can not only obtain accurate three-dimensional spatial scale information of nanoscale materials, but also be used to count the three-dimensional spatial volume density information of internal defects in nanoscale materials. It has important application prospects in the field of precision measurement of nanoscale materials.
[0015] Optionally, S10 specifically includes: using a focused ion beam method to prepare a nanometer-scale needle-tip electron microscope sample of the test material with a circular cross-section, and mounting the nanometer-scale needle-tip electron microscope sample on a transmission electron microscope sample rod.
[0016] Optionally, S20 specifically includes: moving the nanometer-scale needle-shaped electron microscope sample to the center of the field of view of the transmission electron microscope fluorescent screen, taking a transmission electron microscope image of the nanometer-scale needle-shaped electron microscope sample, and measuring the thickness of different areas of the nano-needle tip.
[0017] Optionally, S30 specifically includes: setting the transmission electron microscope optical path to a scanning transmission mode, setting the camera length, the condenser aperture, and the electron energy loss spectrum receiving aperture, moving the transmission electron microscope electron beam to the rear barrel imaging filter, setting the receiving aperture angle according to the camera length and the electron energy loss spectrum receiving aperture, selecting the electron energy loss spectrum line acquisition mode, setting the acquisition time and acquisition step size of the electron energy loss spectrum line scanning image pixel points, performing Ni point scanning and acquisition on the nanometer-scale needle-shaped electron microscope sample from the tip to the bottom, and obtaining the electron energy loss spectrum line scanning image, where i is a positive integer greater than or equal to 1.
[0018] Optionally, S40 specifically includes: selecting any pixel point in the electron energy loss spectrum line scan image, performing zero-peak calibration on the spectrum corresponding to the pixel point, and analyzing the measured thickness from the electron energy loss spectrum line scan image after zero-peak calibration according to the electron beam energy, the receiving aperture angle, and the average effective atomic number of the sample.
[0019] Optionally, S50 is specifically as follows: taking the initial position of collecting the electron energy loss spectrum of the nanometer-scale needle-shaped electron microscope sample as the starting point, taking the distance from the collection position to the starting point as the displacement, fitting to obtain the relationship between the measured thickness and the displacement of the electron energy loss spectrum analysis, fitting to obtain the relationship between the accurate thickness and the displacement measured by the transmission image, and fitting to obtain the calibration relationship between the accurate thickness and the measured thickness.
[0020] Optionally, S60 specifically includes: loading a nanoscale electron microscope sample of the material to be measured for thickness onto a transmission electron microscope sample rod, collecting an electron energy loss spectrum of an area of interest, parsing the actual measured thickness of the nanoscale material from the electron energy loss spectrum after zero-peak calibration, and calculating the precise thickness of the nanoscale material according to a calibration formula.
[0021] Optionally, in step S10, the cross-section of the nanometer-scale needle-shaped transmission electron microscope sample is circular, the cross-sectional roundness is less than 2 nanometers, the cross-sectional diameter ranges from 10 nanometers to 200 nanometers, the tip cone angle is less than 50 degrees, the tip diameter is less than 100 nanometers, and the tip length is greater than 100 nanometers.
[0022] Optionally, in step S30, the working mode of the transmission electron microscope is a scanning transmission electron microscopy analysis mode, the camera length range is 30 microns to 58 microns, the condenser aperture size range is 20 to 150 microns, the electron energy loss spectrum receiving aperture range is 2.5 to 5 mm, the receiving aperture angle range is 12.78 to 50.23 milliradians, the acquisition time range of the acquisition mode pixel point is 0.1 seconds to 5 seconds, the acquisition step range is 1 nanometer to 10 nanometers, and the receiving aperture angle range is 12.78 to 50.23 milliradians.
[0023] Optionally, in step S40, the electron beam energy range is 80 to 300 kilovolts, the receiving aperture angle range is 12.78 to 50.23 milliradians, and the average effective atomic number of the sample is greater than or equal to 1.
[0024] Optionally, in step S60, the thickness of the tested nanoscale material should not be greater than the maximum diameter of the nanoscale needle-shaped electron microscope sample.
[0025] The present application provides an electron microscopic analysis method for measuring the thickness of nanometer-scale materials. This method can achieve wide-range, high-precision, fast and user-friendly sample thickness measurement by refining the operation process and using advanced analysis algorithms, thereby meeting the needs of current scientific research and industrial applications. The beneficial effects of the present application are:
[0026] 1. Precise calibration: This application adopts an innovative method for measuring the thickness of nanoscale materials, which can measure nanoscale materials with a minimum thickness of 0.5 nanometers. The measurement accuracy is improved by up to 28% compared with the electron energy loss spectrum method, realizing the measurement of the thickness distribution of transmission electron microscope samples with nanoscale resolution, and improving the practicality and accuracy of thickness measurement.
[0027] 2. Versatility: This method is not only applicable to analyzing the relationship between the number density of precipitates or defects in nanoscale materials and the thermal treatment state of the material, but can also be used to analyze the three-dimensional volume density of helium bubbles in tritium compounds, revealing the microscopic mechanism of helium bubble initiation and growth.
[0028] 3. Wide applicability: The method of this application is applicable to the precise thickness measurement of various types of samples, including metals, non-metals and non-conductive materials, which greatly expands the application field of traditional thickness measurement technology.
[0029] 4. Strong potential: With its nanometer-scale resolution and wide applicability, this application shows broad application potential in many high-tech fields such as materials science, micro-nano electronics, aerospace, etc., especially for advanced materials research that has extremely strict requirements on thickness measurement. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a microscopic image of the nanometer-scale needle tip of the tritiated sample in Example 1;
[0031] Figure 2 The relationship curve between the measured thickness, the fitted thickness, the accurate thickness and the displacement in Example 1;
[0032] Figure 3 This is a thickness distribution diagram of the tritium film sample after calibration in Example 1;
[0033] In the figure: 1. The relationship curve between the measured thickness and the displacement; 2. The relationship curve between the fitted thickness and the displacement; 3. The relationship curve between the accurate thickness and the displacement. DETAILED DESCRIPTION
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative labor.
[0035] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with specific implementation methods and drawings.
[0036] Example 1
[0037] The electron microscopic analysis method for measuring the nanometer-level thickness of a transmission electron microscope sample proposed in this embodiment comprises the following steps:
[0038] (10) Preparation and loading of nanometer-scale needle-shaped electron microscopy samples
[0039] The focused ion beam method is used to prepare nano-scale needle-tip TEM samples, and nano-scale needle-tip TEM samples with a cross-section close to a circle are obtained. The diameter of the tip front end should be less than 200 nanometers. The TEM sample is mounted on a special TEM sample rod with the needle tip placed along the long axis of the sample rod.
[0040] (20) Accurate thickness measurement of nanometer-scale needle-shaped electron microscope samples
[0041] Move the sample rod to place the nanometer-scale needle-shaped electron microscope sample in the center of the field of view, adjust it to the positive focus state, take a transmission electron microscope image of the nanometer-scale needle tip, and measure the accurate thickness of different areas of the nanometer-scale needle tip.
[0042] (30) Collection of electron energy loss spectra of nanoscale needle-shaped electron microscope samples
[0043] Set the working mode of the transmission electron microscope to the scanning transmission electron microscopy analysis mode, set the camera length range to 30 μm to 58 μm, the condenser aperture size range to 20 to 150 μm, the electron energy loss spectrum receiving aperture range to 2.5 to 5 mm, the receiving aperture angle range to 12.78 to 50.23 mrad, select the electron energy loss spectrum line acquisition mode, set the acquisition time range of the electron energy loss spectrum line scanning image pixel points to 0.1 seconds to 5 seconds, the acquisition step range to 1 nanometer to 10 nanometers, perform Ni point scanning and acquisition from the tip to the bottom of the nanometer-scale needle-shaped electron microscope sample, and obtain the electron energy loss spectrum line scanning image, where i is a positive integer greater than or equal to 1.
[0044] (40) Analysis of the measured thickness of nanometer-scale needle-shaped electron microscope samples
[0045] Select any pixel point in the electron energy loss spectrum scanning diagram, perform zero-peak calibration on the spectrum corresponding to the pixel point, and calibrate the measured thickness based on the electron beam energy range of 80 to 300 kV, the receiving aperture angle range of 12.78 to 50.23 milliradians, and the average effective atomic number of the sample being a positive number greater than or equal to 1.
[0046] (50) Thickness calibration relationship fitting
[0047] Taking the initial position of the electron energy loss spectrum collected by the nanometer-scale needle-shaped electron microscope sample as the starting point, and the distance from the collection position to the starting point as the displacement, the relationship between the measured thickness and the displacement of the electron energy loss spectrum analysis is fitted, the relationship between the accurate thickness and the displacement measured by the transmission image is fitted, and the calibration relationship between the accurate thickness and the measured thickness is fitted.
[0048] (60) Thickness measurement of nanoscale materials
[0049] A nanoscale electron microscope sample of the material to be tested whose thickness is less than the maximum diameter of the nanoscale needle-shaped electron microscope sample is loaded into the transmission electron microscope sample rod, and the electron energy loss spectrum of the area of interest is collected. The actual measured thickness of the nanoscale material is analyzed from the electron energy loss spectrum after zero peak calibration, and the precise thickness of the nanoscale material is calculated based on the calibration relationship.
[0050] The focused ion beam microscope and transmission electron microscope equipment used in this example are as follows:
[0051] (1) Focused ion beam microscopy: A Scios 2HiVac focused ion beam microscope from Thermofisher Scientific, USA, was used to thin the samples and to perform microstructural analysis on the prepared nanometer-scale needle tips and thin-film electron microscopy samples. The acceleration voltage was 2 kV to 30 kV.
[0052] (2) Transmission electron microscopy: The Themis Z double spherical aberration corrected transmission electron microscope (TEM) from Thermofisher Scientific, USA, was used to analyze the sample thickness. The operating voltage was 80-300 kV, the camera length was 30-58 μm, the condenser aperture was 20-150 μm, the electron energy loss spectrum receiving aperture was 2.5-5 mm, and the receiving aperture angle was 12.78-50.23 mrad.
[0053] The experimental results show that the electron microscopic analysis method for measuring the nanometer-level thickness of transmission electron microscope samples in this application is a method that can effectively improve the thickness measurement accuracy. This method overcomes the problems of narrow application range and low measurement accuracy in existing methods. This method analyzes and obtains the thickness surface distribution information of transmission electron microscope samples, which has a significant impact on measuring the three-dimensional volume density of second phases and crystal defects.
[0054] Example 2
[0055] This example analyzes the volume density of needle-shaped helium bubbles in tritium, and the specific steps are as follows:
[0056] a. Preparation and loading of nano-sized needle-shaped electron microscope samples
[0057] A focused ion beam method is used to prepare a tritiated nano-scale needle tip transmission electron microscope sample with a circular cross-section. The cross-sectional roundness of the transmission electron microscope sample is less than 2 nanometers, the cross-sectional diameter ranges from 10 nanometers to less than 200 nanometers, the tip cone angle is less than 50 degrees, and the tip (diameter less than 100 nanometers) is greater than 100 nanometers in length. The transmission electron microscope sample is mounted on a special transmission electron microscope double-tilt sample rod so that the needle tip is placed along the long axis of the sample rod.
[0058] b. Accurate thickness measurement of nanometer-scale needle-shaped electron microscope samples
[0059] Move the nanometer-scale needle-shaped electron microscope sample to the center of the field of view of the transmission electron microscope fluorescent screen, and take a transmission electron microscope image of the nanometer-scale needle-shaped electron microscope sample, such as Figure 1 As shown, the accurate thickness of different areas of the nanometer-scale needle-shaped electron microscope sample is measured.
[0060] c. Collection of electron energy loss spectra of nano-scale needle-shaped electron microscope samples
[0061] Set the working mode of the transmission electron microscope to the scanning transmission electron microscopy analysis mode, set the camera length to 30 microns, the condenser aperture to 20 microns, the electron energy loss spectrum receiving aperture to 5 mm, the receiving aperture angle range to 12.78 to 50.23 milliradians, select the electron energy loss spectrum line acquisition mode, set the acquisition time range of the electron energy loss spectrum line scanning image pixel points to 0.2 seconds, the acquisition step range to 1.5 nanometers, select the center axis of the nanometer-scale tip front end area for 396-point scanning and acquisition, and obtain the electron energy loss spectrum line scanning image.
[0062] d. Analysis of the measured thickness of nanometer-scale needle-shaped electron microscope samples
[0063] Select any pixel point in the electron energy loss spectrum line scan, and perform zero-peak calibration on the corresponding spectrum of the pixel point according to the electron beam energy of 300 kV, the receiving aperture angle range of 50.23 mrad, and the average number of effective atoms of the sample of 8. The measured thickness can be analyzed from the zero-peak calibrated electron energy loss spectrum, such as Figure 2 shown.
[0064] e. Thickness calibration relationship fitting
[0065] Taking the initial position of the electron energy loss spectrum collected by the nanometer-scale needle-shaped electron microscope sample as the starting point, and the distance from the collection position to the starting point as the displacement, the relationship between the measured thickness and the displacement analyzed by the electron energy loss spectrum is fitted, Y=-2.25*10-4*X2+0.49X+53.14, as shown in Figure 2 As shown. The relationship between the accurate thickness and displacement measured by the transmission image is fitted to obtain Y = -198.21*exp(-X / 380.66)+235.69, as Figure 2 As shown, the calibration relationship between the accurate thickness and the measured thickness is obtained by fitting, Y=-349.85*exp(-X / 268.53)+24.65.
[0066] f. Thickness measurement of nanoscale tritium film samples
[0067] The tritiated TEM film sample is loaded into the electron microscope, and the electron energy loss spectrum is collected to obtain the thickness surface distribution data of the area of interest. The thickness surface distribution data is corrected according to the relationship Y=-349.85*exp(-X / 268.53)+324.65 to obtain the thickness surface distribution data as shown in 3.
[0068] g. 3D volume density calculation
[0069] According to the statistical number of helium bubbles (4553), the statistical area (10703 nm2) and the average thickness (125.6 nm), the three-dimensional density of helium bubbles is calculated to be 3.39*10-3 / nm3.
[0070] The test results are as follows:
[0071] Figure 1 The microscopic image of the tritiated nanometer-scale needle-shaped electron microscope sample is shown, and the measured thickness distribution information along the central axis of the nanometer-scale needle-shaped electron microscope sample is provided. Figure 2 The graph shows the relationship between the measured thickness and displacement obtained by electron energy loss spectrum measurement, the relationship between the thickness and displacement fitted by the electron energy loss spectrum, and the relationship between the accurate thickness and displacement. Figure 3 The thickness distribution of the tritium film sample after calibration is shown in Figure 2. Figure 2 It can be seen that the thickness of tritium measured by electron energy loss spectroscopy is higher than the measured value, and the measurement error increases significantly with the increase of the measured thickness, indicating that the value of the three-dimensional density of helium bubbles measured before calibration is lower than the measured value. This discovery is of great value for understanding the development mode of helium bubbles and the mechanism of their rupture process.
Claims
1. An electron microscopic analysis method for measuring the thickness of nanometer-scale materials, characterized in that: The following steps are involved: S10, preparation of nanometer-scale needle-shaped transmission electron microscope samples by focused ion beam method; S20, taking transmission electron microscope images to obtain the accurate thickness of different areas of the nanometer-scale needle tip; S30, collecting electron energy loss spectra of different regions of nanometer-scale needle-tip electron microscope samples; S40, the measured thickness of different regions of the nanometer-scale tip electron microscope sample was analyzed after zero peak calibration of the electron energy loss spectrum; S50, obtaining a calibration relationship between the accurate thickness and the measured thickness through data fitting; S60. Collect electron energy loss spectra of other samples of interest with the same composition as the nano-scale needle-tip electron microscope sample to obtain thickness data, use a calibration relationship to correct the thickness data, and obtain nano-scale thickness measurement of the material.
2. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to claim 1, characterized in that: S10 specifically includes: using a focused ion beam method to prepare a nanometer-scale needle-tip electron microscope sample of a test material with a circular cross-section, and installing the nanometer-scale needle-tip electron microscope sample on a transmission electron microscope sample rod.
3. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to claim 1, characterized in that: S20 specifically includes: moving the nanometer-scale needle-shaped electron microscope sample to the center of the field of view of the transmission electron microscope fluorescent screen, taking a transmission electron microscope image of the nanometer-scale needle-shaped electron microscope sample, and measuring the thickness of different areas of the nano-needle tip.
4. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to claim 3, characterized in that: S30 is specifically as follows: setting the transmission electron microscope optical path to scanning transmission mode, setting the camera length, condenser aperture, and electron energy loss spectrum receiving aperture, moving the transmission electron microscope electron beam to the rear barrel imaging filter, setting the receiving aperture angle according to the camera length and the electron energy loss spectrum receiving aperture, selecting the electron energy loss spectrum line acquisition mode, setting the acquisition time and acquisition step of the electron energy loss spectrum line scanning image pixel points, performing Ni point scanning and acquisition on the nanometer-scale needle-shaped electron microscope sample from the tip to the bottom, and obtaining the electron energy loss spectrum line scanning image, where i is a positive integer greater than or equal to 1.
5. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to claim 4, characterized in that: S40 specifically includes: selecting any pixel point in the electron energy loss spectrum line scan image, performing zero-peak calibration on the spectrum corresponding to the pixel point, and analyzing the measured thickness from the electron energy loss spectrum line scan image after zero-peak calibration according to the electron beam energy, receiving aperture angle, and the average number of effective atoms of the sample.
6. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to any one of claims 1 to 5, characterized in that: S50 is specifically as follows: taking the initial position of collecting the electron energy loss spectrum of the nanometer-scale needle-shaped electron microscope sample as the starting point, taking the distance from the collection position to the starting point as the displacement, fitting to obtain the relationship between the measured thickness and the displacement of the electron energy loss spectrum analysis, fitting to obtain the relationship between the accurate thickness and the displacement measured by the transmission image, and fitting to obtain the calibration relationship between the accurate thickness and the measured thickness.
7. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to claim 6, characterized in that: S60 specifically includes: loading a nanometer-scale electron microscope sample of a material to be measured for thickness onto a transmission electron microscope sample rod, collecting an electron energy loss spectrum of an area of interest, parsing the actual thickness of the nanometer-scale material from the electron energy loss spectrum after zero-peak calibration, and calculating the precise thickness of the nanometer-scale material according to a calibration formula.
8. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to claim 1, characterized in that: In step S10, the cross-section of the nanometer-scale needle-shaped transmission electron microscope sample is circular, the cross-section roundness is less than 2 nanometers, the cross-section diameter ranges from 10 nanometers to 200 nanometers, the tip cone angle is less than 50 degrees, the tip diameter is less than 100 nanometers, and the tip length is greater than 100 nanometers.
9. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to claim 1, characterized in that: In the step S30, the working mode of the transmission electron microscope is the scanning transmission electron microscopy analysis mode, the camera length range is 30 microns to 58 microns, the condenser aperture size range is 20 to 150 microns, the electron energy loss spectrum receiving aperture range is 2.5 to 5 mm, the receiving aperture angle range is 12.78 to 50.23 milliradians, the acquisition time range of the acquisition mode pixel point is 0.1 seconds to 5 seconds, the acquisition step range is 1 nanometer to 10 nanometers, and the receiving aperture angle range is 12.78 to 50.23 milliradians.
10. The electron microscopic analysis method for measuring the thickness of nanometer-scale materials according to claim 1, characterized in that: In the step S60, the thickness of the tested nanoscale material should not be greater than the maximum diameter of the nanoscale needle-shaped electron microscope sample.
